Women in the Ceramic Craft Industry of Mayong Lor: Contribution and Empowerment - Alamsyah, Alamsyah; Angga, Vicky Verry (Proceedings International Conference of Culture and Sustainable Development; Vol 2 (2024): PROCEEDINGS ICOCAS, 2024)
Mayong Lor Village, Jepara has long been known as a centre for ceramic crafts. Women play a crucial role in this industry, yet their contributions are often less visible. This study aims to reveal women's involvement in the ceramic production process, its impact on empowerment, and the challenges and opportunities faced. This research uses a qualitative method with data collection through observation, in-depth interviews, and literature study. The main informants are women ceramic craftsmen in Mayong Lor. The results show that women have a very important role in the entire ceramic production process, from material preparation to finishing. Their involvement has contributed significantly to the family economy and the preservation of local culture. However, women also face challenges such as limited access to capital, training and markets. Women in Mayong Lor are one of the main pillars in the ceramic craft industry. Empowering female workers is crucial to maintaining tradition, improving welfare and advancing the local economy. A comprehensive empowerment strategy, including increased access, network building, and policy advocacy, needs to be implemented to strengthen the role of women in the Mayong Lor ceramic craft industry.
Keywords: women, ceramics, Mayong Lor, empowerment